Supramodality within the visual cortex : a functional connectivity analysis of the blind and sighted brain - Wong, Ern (Nanyang Technological University, 2021)
Extensive reorganisation of brain networks can occur following the loss of sight. However, previous studies have shown that such massive reorganisation in the visual cortex does not occur in a part of the occipito-temporal cortex, such that the functions of high-order visual regions are preserved. If these areas in the high-order visual cortex develop their functions regardless of visual experience, their associated networks are also expected to develop similarly irrespective of vision loss. The present thesis aims to examine this possibility by testing the action-observation network (AON) that involves a high-order visual cortex called the extrastriate body area (EBA). The EBA is more sensitive to the visuo-haptic presentation of body parts than other categories of objects and its superior part shows the same body sensitivity regardless of visual experience and sensory modality. Here, a context-dependent functional connectivity analysis was conducted on the data of a functional MRI study in which sighted and blind participants underwent a haptic object-identification task. The psychophysiological interaction analysis (PPI) was performed with activity in the early visual cortex (V1) and the supramodal part of the EBA as seed regions and with hand sensitivity as psychological factors. The PPI analysis on the supramodal part of the right EBA (sREBA) showed common PPI effects mainly in the inferior parietal lobule, inferior frontal gyrus, superior parietal lobule, sensorimotor cortices, superior frontal gyrus, caudate nucleus, and fusiform gyrus, regardless of visual experience. By contrast, analyses on V1 showed no significant effects in the EBA in both blind and sighted groups. The implications of these findings were discussed.